Elevated GABRP expression is correlated to the excessive autophagy in intrahepatic cholestasis of pregnancy - Ruihong Dong; Yayi Hu; Qian Chen; Dan Shan; Yuxia Wu (Heliyon, 2023)
In intrahepatic cholestasis of pregnancy (ICP) patients, high concentrations of bile acids altered the normal maternal-fetal-unit physiological condition and could bring negative influence on placenta functionality. GABRP is the pi subunit of the gamma-aminobutyric acid type A receptor (GABAA) and plays pivotal role in regulating GABAA receptor's physiological function. Here we presented evidence that increased expression of GABRP in parallel with autophagic biomarkers, LC3 and ATG14, in patients with ICP. Methods: A total of 27 participants, including 18 ICP patients and 9 healthy pregnancies were recruited according to strict inclusion criteria. Placentas of ICP patients and controls were collected immediately after cesarean section before labor onset. GABRP and autophagic markers expression in placenta were investigated by immunohistochemistry (IHC), RT-qPCR, and Western blot. Results: The neonatal birthweight and gestational weeks were significantly lower in severe ICP group, while the hepatic enzymes were elevated in ICP group. Semiquantitative analysis of IHC revealed the AOD of GABRP in severe ICP patients was higher than that in mild ICP patients and control pregnancies. Western blot and RT-qPCR analysis both indicated that the expression of GABRP and ATG14 were significantly elevated in severe ICP patients. Moreover, GABRP was correlated with TBA (r = 0.64, p < 0.05), ATG14 (r = 0.87, p < 0.05), direct bilirubin (r = 0.54, p < 0.05), ALT (r = 0.72, p < 0.05), and AST (r = 0.67, p < 0.05). Conclusion: There were elevated expression of GABRP, ATG14 and LC3 in ICP placentas compared with uncomplicated pregnancies. The expression of GABRP was associated with autophagy and was correlated with the TBA levels.